Creativity and Innovation Management for Increasing Entrepreneurship Performance in the New Normal Era in East Bolaang Mongondow District - Trang, Irvan; Murni, Sri; Dotulong, Lucky O. H. (Archives of Business Research, 2023)
Human resources are an important factor in an organization because they play a role in planning, implementing and controlling or in other words as system managers in an organization.Quality human resources are human resources who have creativity and innovation at work. An Entrepreneur is a human resource who is directly involved in carrying out their business activities. To create that, entrepreneurs need to carry out creativity and innovation in order to improve their performance in maintaining and developing their business. This is of course in line with the current phenomenon, where many businesses are bankrupt, closed, out of business in the current new normal era of the Covid 19 pandemic, including in East Bolaang Mongondow Regency, where there are many entrepreneurs engaged in in mining, marine agriculture as well as a variety of other different businesses affected by the outbreak. The purpose of doing this research is to analyze and study and develop a variable and instrument that is able to identify indicators that influence the increase in the performance of entrepreneurs in East Bolaang Mongondow Regency. The stages of the method used in the approach and achievement of this research are by observation, identifying the population, the sample in this case the respondents (entrepreneurs) in East Bolaang Mongondow Regency, using the survey method, distributing questionnaires and giving open questions to get the best results. accurately, then process the data and evaluate the results obtained for seminars and publication.